Impact of pavement friction decay on speed limits and autonomous vehicles: A theoretical and experimental study - Filippo Giammaria Praticò (Journal of Road Engineering)
Commonly, the standards for the geometric design of roads refer to a given set of values for the friction coefficient (longitudinal and transverse friction). These ''reference'' values imply corresponding visibility sights, curvature radii, and speed limits. Unfortunately, not only do these reference values not correspond to a given standard to measure them, but nothing is said about the decrease of the posted speed limit (variable speed limits) when roads become slippery and lanes for autonomous vehicle (AV) are concerned.Furthermore, the same assessment of the friction coefficient has plenty of uncertainties due to measurement device, temperature, location, time passed from the construction, alignment-related variables (e.g., curve, tangent, transition curve, convexity/crests or concavity/sags, longitudinal slope, superelevation, and ruling gradient), and supplementary singularities such as joints and bridge approaches. All the issues above may harm road safety and the complexity of forensic investigations of pavements.Consequently, this study's objectives were confined to (1) carrying out friction measurements and analyzing the problem of friction decay over time; (2) setting up a method to lower the speed limits where friction decays are detected; (3) setting up a method to handle friction decays for autonomous vehicles. Results demonstrate that: (1) a power law describes how the speed limits are affected by friction; (2) for speeds up to 170 ​km/h, due to the lower reaction time, AV reaction distance is lower, which benefits AV traffic (lower stopping distance); (3) on the contrary, for higher values of friction and higher speeds, under the hypothesis of having the same reaction time law for non-AV (NAV) (i.e., decreasing with the initial speed), AV speed limits become lower than NAV speed limits; (4) not only do comfort-based speed profiles for AVs bring higher braking distances, but also, in the median part (of the deceleration process), this could pose safety issues and reduce the distance between the available and the needed friction.